Synchronisation and desynchronisation at the time of the smartphone - Hylland Eriksen, Thomas (Antropologia Pubblica, 2024)
It just took a little over a decade for the smartphone to conquer the world following its introduction on the world market in 2007. Just fourteen years later, this ubiquitous device has virtually become an extension of the body for hundreds of millions of people.This lecture explores some of the ways in which temporality has been affected by the penetration of the smartphone into people’s life-worlds. There are very substantial variations, and the lecture takes on both the variations and the generic, structural features of the smartphone, which apply in comparable ways everywhere, although they are expressed in specific, locally embedded ways in different societies.The smartphone has affected the rhythms of everyday life. Formerly, appointments would typically be made days or weeks ahead. No micro-adjustment was possible, whereas it is now common, and has entered into everyday routines in European cities, to send a text if one is a little late for an encounter. Before this possibility existed, there was a need for greater flexibility. Conversely, you were free when you were not in and available, and allowed to fill the temporal gaps with anything or nothing. The temporal flexibility was, in other words, greater before the mobile internet, while the spatial flexibility has increased. In the lecture, the clash between the immediacy, miniaturisation and compression of the smartphone, on the one hand, and the other, often slower rhythms characteristic of other domains, are explored, along with the paradoxes of simultaneous synchronisation and desynchronisation.